PENGARUH KUALITAS LAYANAN BERBASIS TEHNOLOGI INFORMASI (TI) TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN BONDOWOSO - Fathorrasi Fathorrasi; Suwignyo Widagdo; Yuniorita Indah Handayani (RELASI : JURNAL EKONOMI, 2022)
Entities both business and public, will improve the quality of service with dimensions that are well applied so that it becomes the key to success in the business and public sector. Good quality service will provide customer satisfaction. Customer satisfaction is the key to business success. Related research to discuss and analyze the effect of services quality based on Information Technology to customer satisfaction of the Regional Water Supply Company of Bondowoso Regency. The data used in this study are primary data obtained through questionnaires. The population of this study is active customers in the service area of ​​the Regional Water Supply Company of Bondowoso Regency with a total sample of 100 people and accidental sampling. For data analysis, the authors used multiple linear regression analysis. Based on the results of the analysis, it can be stated that simultaneously Information Technology (IT) based service quality variables consisting of Reliability, Tangible, Assurance, Empaty and Responsiveness affect customer satisfaction in the Regional Water Supply Company (PDAM) of Bondowoso Regency. Partially, the variable quality of service based on Information Technology (IT) consisting of Reliability, Tangible, Assurance, and Responsiveness affects customer satisfaction in the Regional Water Supply Company (PDAM) of Bondowoso Regency. Where as the variable quality of service based on Information Technology (IT) measured by Empathy partially did not affect customer satisfaction in the Regional Water Supply Company (PDAM) of Bondowoso Regency. Variables in service quality based on Information Technology (IT) as measured by reliability are the dominant variables in influencing the level of customer satisfaction in the Regional Water Supply Company (PDAM) of Bondowoso Regency. Keywords: Service Quality, Reliability, Tangible, Assurance, Empaty Responsiveness, and Customer Satisfaction